Stuck situations in morbidly adherent placenta: how to tackle? - Dua, Manvi; Arya, Sangeeta; Pandey, Kiran; Verma, Anil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Morbidly adherent placenta is associated with high maternal morbidity and mortality. Its increased prevalence seems to be proportional to the increasing number of caesarean sections. In this study the presentation and management of 32 cases was reviewed with morbidly adherent placenta and maternal and perinatal outcomes from 2014 to 2016, at the hospital. Methods: Study type was retrospective. We reviewed clinical information from patients’ case sheets regarding the risk factors, preparations prior to cesarean section, intraoperative and postoperative complications. Results were interpreted and conclusions were withdrawn. Results: Among the 32 cases, 28 were diagnosed prenatally while 4 were diagnosed intraoperatively. Out of 28 patients, 5 patients were diagnosed early between 14 and 18 weeks of gestational age and other 23 were diagnosed during third trimester by ultrasonography. Caesarean hysterectomy was required in 28 cases.4 were managed conservatively, out of which hysterectomy proved to be necessary in the postpartum period because of severe secondary postpartum hemorrhage in 2 cases. Average no of hospital stay is 10 days ranging from 8-18 days. Conclusions: Prenatal diagnosis of morbidly adherent placenta is essential to plan for the better maternal and perinatal outcome. The decision to perform a cesarean hysterectomy or conservation of uterus (using balloon tamponade or putting haemostatic sutures) is based on the extent of infiltration, the patient’s hemodynamic status, and her desire for future pregnancy. The risk of infection and severe hemorrhage remains high if conservative management is chosen and requires prolonged close monitoring postoperatively. Ideally all the cases should be electively planned and operated by senior surgeon and experienced assistants with senior anesthetist, urosurgeon and physician, with full backup of ICU and blood bank.